Blood–Brain Barrier Is the Major Site for a Rapid and Dramatic Prostanoid Increase upon Brain Global Ischemia. Issue 1 (8th December 2019) - Seeger, Drew R.; Golovko, Svetlana A.; Golovko, Mikhail Y.
Abstract: We and others have demonstrated a rapid and dramatic increase in brain prostanoids upon decapitation‐induced brain global ischemia and injury. However, the mechanism for this induction, including the cell types involved, are unknown. In the present study, we have validated and applied a pharmacological approach to inhibit prostanoid synthesis in the blood–brain barrier including endothelial cells. Our results indicate that a nonspecific cyclooxygenase (COX) inhibitor, ketorolac, does not pass the blood–brain barrier and does not enter red blood cells but penetrates endothelial cells. Ketorolac treatment did not affect basal prostanoid levels but completely prevented prostanoid induction upon global ischemia. These data indicate that basal prostanoids are synthesized in brain parenchyma cells, while inducible prostanoids are synthesized in the blood–brain barrier, most likely in endothelial cells. However, future studies with cell and COX isoform‐specific gene ablation are needed to further validate this conclusion. These findings identify endothelial cells as a possible target for the development of pharmacological approaches to selectively attenuate inducible prostanoid pools without affecting basal levels under brain ischemia, trauma, surgery, and other related conditions.